Synthesis of nitrogen heterocycles via transition metal catalyzed reductive cyclizations of nitroaromatics. - O'dell, David K. (My University, 2003)
This research focuses on applying a catalyst system discovered in this laboratory, for the intermolecular allylic amination of alkenes with nitrobenzenes, to the synthesis of nitrogen heterocycles via an intramolecular reaction. The catalysts investigated in this study were of the general type [Cp(CO) 2M]2, where M = Fe or Ru. The use of these catalysts with CO pressure (50 atm) allows for the reductive cyclization of o-nitro styrenes to indoles and o-nitroenones to 4-quinolones in moderate to good yield. The reductive cyclization of the Baylis-Hillman adducts of 2-nitro benzaldehydes and acrylates were found to produce indoles and N-formyl indolines in poor yield, in marked contrast to previously reported cyclizations of these substrates with conventional nitro reductants. Functionalization of these o-nitro Baylis-Hillman adducts in a variety of ways led to the discovery that the Baylis-Hillman acetates produce quinolines selectively in good yields (47--67%) under somewhat mild conditions (7 atm CO, 150° C, 10 mol [Cp*(CO)2Fe]2, .011M substrate in dioxane, where Cp* = pentamethylcyclopentadienyl). Limited mechanistic studies (crossover experiments with a mixed Cp ligand dimer) implicate the possible involvement of 17 e-radicals from dissociation of the dimeric catalyst under our reaction conditions. It has also been found that 2-nitro ketoximes cyclize to 1H-indazoles under similar conditions in poor to good yield (26--85%).
Keywords: Ring formation (Chemistry); Amines.; Chemistry, Inorganic.; Nitroaromatic compounds.; Chemistry, Organic.